Information security of children and adolescents in understanding parents and teachers - Bovina I.B.; Dvoryanchikov N.V.; Budykin S.V. (Психология и право, 2015)
The article presents the first part of the work devoted to the study of ordinary representations of parents and teachers about information security of children and adolescents. It is about addressing the problem of information security of children and adolescents, discuss the effects of observing violence in the mass media on the subsequent behaviour of viewers, refers to directing television roles on the example of transfer schemes by S. Milgram in the context of television game (experiment J. L. Beauvois with colleagues). This paper examines the impact on users has the Internet, discusses the main directions of action in relation to ensuring information security of children and adolescents, focusing on psychological aspects of the concept of information security of children, demonstrates the importance of studying "naive theories" that govern the actions aimed at ensuring information security of children. The authors explain the prospect of studying problems of information security of children in the framework of the theory of social representations.